THE ROLE OF VOUCHER SALES INFORMATION SYSTEM ON HOTEL RESERVATION (Case Study at PT KAHA Tours & Travel Branch Office Malang ) - Choirul Huda Tommi Prastawa (Jurnal Administrasi Bisnis, 2014)
Information is a valuable asset and has an important role for an organization or a company. The rapid progress of computer technology at this time make computer as a data processors are reliable in both of application field. In other side of travel, especially travel agencies both of domestic and international, development rapidly. In practice, a travel agents must use system information, which the system can support the marketing division effectively and efficiently. By using the application of the system of sales information on the process of hotel reservation voucher as expected fed decision support system can be help performance marketing travel agent itself in sales practically, therefore the service sales by travel agents hotel vouchers to consumers growing optimally.  In other side, the information system of reservation process on the sale of hotel vouchers required to evaluate and improve role of voucher sales information system on hotel reservation at PT KAHA Tours & Travel branch office Malang. Key word : Information System, Role, Voucher Sales Information System, Reservation Abstraksi Informasi merupakan aset berharga dan memiliki peranan penting bagi suatu organisasi atau perusahaan. Kemajuan pesat teknologi komputer saat ini membuat komputer sebagai prosesor data yang handal dalam kedua bidang aplikasi. Di sisi lain dari perjalanan, terutama perjalanan lembaga baik dari dalam negeri dan internasional, pengembangan cepat. Dalam prakteknya, sebuah agen perjalanan harus menggunakan sistem informasi, dimana sistem dapat mendukung divisi pemasaran secara efektif dan efisien. Dengan menggunakan aplikasi sistem informasi penjualan pada proses voucher pemesanan hotel seperti yang diharapkan fed sistem pendukung keputusan dapat membantu kinerja pemasaran agen perjalanan itu sendiri dalam penjualan praktis, sehingga penjualan layanan dengan voucher agen perjalanan hotel ke konsumen tumbuh optimal.  Di sisi lain, sistem informasi proses pemesanan atas penjualan voucher hotel yang dibutuhkan untuk mengevaluasi dan meningkatkan peran sistem informasi penjualan voucher untuk reservasi hotel di PT KAHA Tours & Travel kantor cabang Malang. Kata kunci: Sistem Informasi, Peran, Sistem Informasi Penjualan Voucher, Reservation